Structuring Tenses of English by Islamic Higher Education Students: A Case Study at Universitas Sains Alqur’an - Rofik, Abdur; Sahid, Sahid (Universitas Malikussaleh, 2019)
The aims of this study are to reveal errors in structuring tenses and to find out errors of surface structures committed by Islamic Higher Education Students of Universitas Sains Alqur’an, Wonosobo. Subject of the study is 28 students of Islamic Relegion Education Study Program of Tarbiyah Sciences and Teacher Training Faculty of Universitas Sains Alqur’an, Wonosobo in the first semester of the 2018/2019 Academic Year. Data collecting was conducted through written work instruments. In analyzing the data, the writer reads the data sources, indentifies the errors, classifies them, and especially for tense errors, the writer adds the step of data analysis, namely calculating the errors to find the percentage. The results convey that with regard to tense aspects, the student errors involve simple present 13,54%, present progressive 30,2%, present perfect 28,64%, and present perfect progressive tense 27,6%. Then, with regard to surface structures, the factors of errors committed are omission, addition, misformation, and misordering.